SIMULATING RUSSIA'S AND OTHER LARGE ECONOMIES' CHALLENGING AND INTERCONNECTED TRANSITIONS - Seth G. Benzell; Eugene Goryunov; Marija Kazakova; Laurence J. Kotlikoff; Guillermo LaGarda; Kristina Nesterova; Andrey Zubarev (NBER, 2015)
This paper develops a large-scale, dynamic life-cycle model to simulate Russia's demographic and fiscal transition under favorable and unfavorable fossil-fuel price regimes. The model includes Russia, the U.S., China, India, the EU, and Japan+ (Japan plus Korea). The model predicts dramatic increases in tax rates in the U.S., EU, India, and Russia. Indeed, the increases are so large as to question their political feasibility let alone their actual collection given the potential for tax avoidance and tax evasion.
Keywords: F0; F20; H0; H2; H3; J20; 330; economy; transitions